Effects of quinoa on cardiovascular disease and diabetes: a review - Zhang, He; Li, Ruiqi (Frontiers in Nutrition, 2024)
Quinoa is an annual dicotyledonous plant belonging to the genus Chenopodiaceae. As a functional healthy food with outstanding nutritional value, quinoa contains not only a balanced proportion of amino acids but also higher contents of protein, unsaturated fatty acids, vitamins, and minerals (K, P, Mg, Ca, Zn, and Fe) than most cereal crops. Quinoa is also rich in active ingredients, such as polyphenols, flavonoids, saponins, polysaccharides, peptides, and ecdysone, which provide balanced nutrition, enhance the body function, regulate blood sugar, decrease blood lipid, increase anti-oxidation and anti-inflammatory action, and prevent and treat cardiovascular diseases. Thus, quinoa is especially suitable for people suffering from chronic diseases, such as diabetes, hypertension, hyperlipidemia, and heart disease, and for the elderly people. Because of its comprehensive nutritional value and edible functional characteristics, quinoa is better than most grains and has become a highly nutritious food suitable for human consumption. This article reviews the active ingredients and physiological functions of quinoa, aiming to provide a reference for further research and its utilization in food, healthcare, and pharmaceutical research and development.